Analisis Prestasi Akademik Mahasiswa Teknik Elektro Ditinjau dari Latar Belakang Pendidikan dan Jalur Masuk - Mardita, Enchi; Usmeldi, Usmeldi (Jurnal Pendidikan Teknik Elektro, 2024)
This research is motivated by the academic achievement of students at the UNP Electrical Engineering Department in terms of educational background and entry routes, which have a significant influence. This research aims to analyze students' academic achievement at the UNP Electrical Engineering Department in terms of educational background and entry routes. This research uses a quantitative approach with a comparative research type. The subjects of this research were students of the Electrical Engineering Education study program entering 2020, totaling 80 people. The type of data and data collection is in the form of documentation of the IP scores of students in the Electrical Engineering Education study program and inferential data analysis. The research results show that the IP scores of students from the Electrical Engineering Education study program have a significant influence on academic achievement. The researchers' suggestions are: 1) lecturers, should provide more influence and motivation and arouse students' interest in learning to continue to get a better GPA. 2) For students, it is hoped that they will increase their interest, and motivation and choose a friendship environment that can make them more positive and productive so they can have good achievements. 3) For students, it is hoped that they will increase their interest, and motivation and choose a friendship environment that can make them more positive and productive so that they can have good achievements.